STUDY OF PHYSICAL AND CHEMICAL CONTENT OF TEMPEH FACTORY LIQUID WASTE IN BEKASI DISTRICT - Azteria, Veza; Veronika, Erna; Irfandi, Ahmad (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2025)
The tempeh industry in Indonesia is a traditional household industry. The production waste is generally discharged directly into water bodies without prior treatment. This study aims to identify the level of pollution caused by tempeh liquid waste physically and chemically. Analysis was carried out with laboratory tests to determine the levels of pH, TSS, BOD, COD, colour, and odour produced. This study was conducted at 3 large tempeh industries in Bekasi from January to April 2025. The results of laboratory tests showed that the chemical and physical parameters did not meet the quality standards of the Minister of Environment Regulation No. 5 of 2014. COD measurements found 1 point that did not meet the quality standards of 629.47 mg / l, TSS inlet 221 mg / l and TSS outlet 65 mg / l, the highest BOD 22.50 mg / l due to the addition of chemicals to tempeh to accelerate fermentation. This study uses inferential statistical analysis. The pH parameters for both the inlet and outlet are <6.5. Discharge of waste directly into rivers results in an unpleasant odour from fermented soybeans and organic matter. Tempeh wastewater is recommended for processing organic fertiliser or biogas from anaerobic fermentation.